2017
DOI: 10.19185/matters.201611000018
|View full text |Cite
|
Sign up to set email alerts
|

BIN1 localization is distinct from Tau tangles in Alzheimer’s disease

Abstract: BIN1 is the second most significant Alzheimer’s disease (AD) risk factor gene identified through genome-wide association studies. BIN1 is an adaptor protein that can bind to several proteins including c-Myc, clathrin, adaptor protein-2 and dynamin. BIN1 is widely expressed in the brain and peripheral tissue as ubiquitous and tissue-specific alternatively spliced isoforms that regulate membrane dynamics and endocytosis in multiple cell types. The function of BIN1 in the brain and the mechanism(s) by which AD-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…While this study focused the expression of BIN1 in three major cell types in the grey matter of DLPFC (https://doi.org/10.1101/566307), the expression of BIN1 by mature oligodendrocytes and its involvement in oligodendrocyte myelination has been described in the white matter [12]. These investigators reported that oligodendrocytes, which are enriched in white matter, mainly express BIN1 isoform 9 [42], which could explain why our exon-specific antibodies did not detect BIN1 isoforms expressed by oligodendrocytes, since exons 7, 11, 13 or 16 are not contained within isoform 9.…”
Section: Discussionmentioning
confidence: 99%
“…While this study focused the expression of BIN1 in three major cell types in the grey matter of DLPFC (https://doi.org/10.1101/566307), the expression of BIN1 by mature oligodendrocytes and its involvement in oligodendrocyte myelination has been described in the white matter [12]. These investigators reported that oligodendrocytes, which are enriched in white matter, mainly express BIN1 isoform 9 [42], which could explain why our exon-specific antibodies did not detect BIN1 isoforms expressed by oligodendrocytes, since exons 7, 11, 13 or 16 are not contained within isoform 9.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, cis-eQTLs within 1Mb window cover that region and extend through non-zero LD effect of CYP27C1 to nearly 2Mb around the GWAS locus (Fig 3e). The contribution of BIN1 to AD is somewhat controversial [65][66][67] , and we expect follow-up mediation analysis with cell type-specific eQTLs will further clarify the mechanisms.…”
Section: Cammel Finds New Genes In Ad Gwas Locimentioning
confidence: 96%
“…The exact consequence of the LOAD-associated SNPs identified at the BIN1 locus remains unknown. Previous studies have reported conflicting findings on BIN1 protein expression levels in AD (9 -12) and how it correlates with amyloid and tau pathology (9,10,(13)(14)(15), whereas BIN1 mRNA levels have been shown to be altered in disease and correlate with age of disease onset and disease duration (16).…”
mentioning
confidence: 99%